WS6 Induces Adult Hippocampal Neurogenesis in Correlation to its Antidepressant Effect on the Alleviation of Depressive-like Behaviors of Rats. (1st October 2021) - Zhang, Heao; Xiang, Lin; Yang, Liang; Wu, Si; Liu, Sisi; Zhao, Juan; Song, Da; Ma, Congxuan; Ni, Junjun; Quan, Zhenzhen; Liang, Jianhua; Qing, Hong
Highlights: WS6 improves the depressive-like behaviors of CUMS model rats. WS6 enhances the hippocampal neurogenesis in the CUMS model rats. WS6 enhances the GABA signaling in the hippocampus of CUMS model rats. WS6 induces dendritic density in the hippocampus of CUMS model rats. Abstract: Major depressive disorder (MDD) is one of the most common psychiatric disorders. However, the effective drugs for MDD have not yet been developed. WS6 is originally designed with a similar structure as Resveratrol and Pterostilbene. The present study aims to investigate the neuroprotective and ameliorating effects of WS6 treatment in a rat model of chronic unpredictable mild stress (CUMS) induced depression. The results show that CUMS is effective in producing depressive-like behavior in rats as indicated by decreased responses in the locomotor activity, sucrose preference test and increased immobility time. However, WS6 treatment significantly ameliorated these behavioral alterations associated with CUMS-induced depression. Moreover, the reduction in neurogenesis, GABAergic neurons, dendrite complexity, spine density and synaptic plasticity-associate protein 95 (PSD95) by CUMS can be reversed by treatment with WS6. Taken together, this study highlights the neuroprotective and antidepressant-like effects of WS6 against CUMS-induced depression, and suggest a possible mechanism for this protection via changes in neurogenesis within the hippocampus. These finding reveal the therapeutic protection of WS6 for use in clinical trials in the treatment of neuronal deterioration in MDD.